Causality and “the mental” - Jennifer Hornsby (Humana.Mente: Journal of Philosophical Studies, 2015)
Many analytic philosophers of mind take for granted a certain (broadly Humean) conception of causality. Assumptions deriving from that conception are in place when they problematize what they call mental causation or argue for physicalism in respect of the mental. I claim that a different (broadly Aristotelian) conception of causality is needed for understanding many ordinary causal truths about things which act, including truths about human, minded beings — sc. rational beings who lead lives.